Ethno-Cultural Aspects of the Entrepreneurship and Employment of the Population in the Rebublic of Sakha (Yyakutiya) - Агата Местникова (Journal of Economic Sociology, 2010)
The main idea of the paper is with the help of socio-cultural approach to show the impact of the ethno cultural factors on the peculiarities of economy and economic behavior of Sakha population. The author tries to tackle the following issues: 1) basics of the beliefs system of the Sakha population that affect the everyday life economic behavior; 2) elements of the traditional economic behavior of Sakha population through the ethnic folk literature (proverbs); 3) the peculiarities of the working behavior of the population; 4) the impact of ethno-cultural factors on business development in the region.